Sequência didática de Ciências para as séries iniciais: a água no ambiente - Costa e Silva, Alessandra Dias (2017)
The teaching and learning of Natural Science in primary school are fundamental, since provide instruments that allow children to understand the world and the society we live in, nevertheless, researches reveal some difficulties that teachers are facing in this subject. Building on this issue, this work seek to analyze the contribution of a didactic sequence (DS), based on the theme Water in the Environment, to assist the work of the teachers of the initial series. This work has two linked parts: the elaboration and propagation, through social network Facebook, of the DS, which, in turn, was published on a Blog; and a research that was accessed by some teachers in the same Blog who answered a survey. In order to underpin this work, it was chosen the sociocultural theory of Vygotsky and, the three pedagogical moments of Delizoicov and Angotti. The research was delineated as both qualitative and quantitative, and its instrument refers to a virtual questionnaire related to the professional profile, academic background, teaching of Sciences, and the strategies used in the sequencing method. For the qualitative analysis it was used the content analysis of Bardin. The results of the research point to the importance of provisioning subsidies in order to assist the work of primary school teachers, who usually are generalists, and to search for innovating methodological strategies, as a focus in Science Technology and Society (STS), interdisciplinarity, Teaching by Investigation and the use of Information and Communications Technology (ICT). Furthermore, the research reveals the need of increasing the development of studies with the goal of contributing for the teaching and learning in primary school.